Distal Symmetric Polyneuropathy Pain in Diabetes Mellitus - Daniella Silva Oggiam; Juliana Vallim Jorgetto; Guilherme Luiz Chinini; Denise Myuki Kusahara; Mônica Antar Gamba (Aquichan, 2021)
Objective: To evaluate neuropathic pain (NP), its intensity, and complications in people with type 2 diabetes mellitus (T2DM) in a city of eastern São Paulo.